Intracellular Staphylococcus aureus and host cell death pathways - Soe, Ye Mon; Bedoui, Sammy; Stinear, Timothy P.; Hachani, Abderrahman (Cellular microbiology, 2021)
Staphylococcus aureus is a major opportunistic human pathogen that is globally prevalent. Although S. aureus and humans may have co‐evolved to the point of commensalism, the bacterium is equipped with virulence factors causing devastating infections. The adoption of an intracellular lifestyle by S. aureus is an important facet of its pathogenesis. Occupying a privileged intracellular compartment permits evasion from the bactericidal actions of host immunity and antibiotics. However, this localization exposes S. aureus to cell‐intrinsic processes comprising autophagy, metabolic challenges and clearance mechanisms orchestrated by host programmed cell death pathways (PCDs), including apoptosis, pyroptosis and necroptosis. Mounting evidence suggests that S. aureus deploys pathoadaptive mechanisms that modulate the expression of its virulence factors to prevent elimination through PCD pathways. In this review, we critically analyse the current literature on the interplay between S. aureus virulence factors with the key, intertwined nodes of PCD. We discuss how S. aureus adaptation to the human host plays an essential role in the evasion of PCD, and we consider future directions to study S. aureus–PCD interactions.